Coherent Measures of Risk from a General Equilibrium Perspective - Péter Csóka; Jean-Jacques Herings; László Á. Kóczy (Hungarian Academy of Sciences, Institute of Economics, 2006)
Coherent measures of risk defined by the axioms of monotonicity, subadditivity, positive homogeneity, and translation invariance are recent tools in risk management to assess the amount of risk agents are exposed to. If they also satisfy law invariance and comonotonic additivity, then we get a subclass of them: spectral measures of risk. Expected shortfall is a well-known spectral measure of risk is. We investigate the above mentioned six axioms using tools from general equi- librium (GE) theory. Coherent and spectral measures of risk are compared to the natural measure of risk derived from an exchange economy model, that we call GE measure of risk. We prove that GE measures of risk are coherent measures of risk. We also show that spectral measures of risk can be represented by GE measures of risk only under stringent conditions, since spectral measures of risk do not take the regulated entity's relation to the market portfolio into account. To give more insights, we characterize the set of GE measures of risk.
Keywords: D51; G10; G12; 330; Coherent Measures of Risk; General Equilibrium Theory; Exchange Economies; Asset Pricing; Allgemeines Gleichgewicht; Risikomanagement; Risiko; Messung; CAPM